Krisis keuangan Indonesia 1997 dan intervensi IMF suatu kajian ekonomi politik - Endang Sih Prapti (Economic Journal of Emerging Markets, 1997)
Thera are many approaches used by analysist to analize the effect of the monetary crisis in Indonesia lately. As shown in this article, Endang Sih Prapti uses a political economic perspective to analize the crisis.